Postmodern Aesthetic Crisis and the Relevance of Iqbal’s Philosophy of Art - Jami, Jamil Asghar; Butt, Muhammad Iqbal (Islamic Studies, 2016)
Under the rubric of postmodern art, a conglomeration of theories emerged since the beginning of the twentieth century—dadaism (later, neo-dadaism), conceptual art, lowbrow art, installation art, pop art, telematic art, digital art and so on. Despite this plethora of theories in an information-flooded age, of late, the contemporary world of art seems to have fallen into a state of agitated confusion. A growing number of critics, theorists, sociologists and historians of art are voicing their concerns about what they see as the postmodern crisis of art. Many of these writers have posited a banality and a mock seriousness which, to them, has come to settle over the horizons of our art. It is here where Iqbal’s philosophy becomes relevant and offers the promise of alleviating what some of the leading contemporary art critics have seen asapathy and angst of postmodern art and restoring it hope and ecstasy. It has been contended that aesthetics propounded by Iqbal locates art at the center of our existential scheme of things and instead of denying the realness and authenticity of art, it takes them as foundational to the very nature and function of art. Art, not as a Platonic imitation but as a creative accomplishment, constitutes the bedrock of Iqbal’s aesthetics. It is this aesthetics which has the potential to cure postmodern art of much of its angst and inconsequence pointed out by such prominent art critics as Stephen Hicks, A. C. Danto, Timothy Bewes, Donald Kuspit, Manfred Stanley and Alan Kaprow, among a host of others.